Successful management of a distal clavicular fracture using Titanium elastic nail (TEN) fixation - Mazen Abdalla, MD; Mohammad M. Jaber, MD; Laith Qasarweh, MD; Yazid Atatri, MD; Soud M.S. Deek, MD; Basel Musmar, MD (Radiology Case Reports, 2024)
This case report presents a unique instance of a 25-year-old male patient successfully treated with Titanium elastic nail (TEN) for a distal clavicle fracture, a method typically reserved for midshaft clavicle fractures. Distal clavicular fractures, constituting 12%-15% of all clavicle fractures, often necessitate surgical intervention to avoid complications such as malunion and persistent pain. While standard surgical therapies include Kirschner wire and hook plate fixation, this case explores the benefits of TEN, known for minimal tissue disruption and faster recovery. The patient, who suffered a severe left shoulder injury after falling, underwent a minimally invasive TEN procedure. Post-surgery, he showed a significant reduction in pain and improvement in shoulder mobility, with radiographic evaluations confirming successful fracture reduction and stable fixation. The case underscores the potential of TEN as a viable alternative for distal clavicular fractures, though further research is needed to establish comprehensive guidelines for its application.